2021
DOI: 10.1186/s13195-020-00743-x
|View full text |Cite|
|
Sign up to set email alerts
|

The molecular tweezer CLR01 improves behavioral deficits and reduces tau pathology in P301S-tau transgenic mice

Abstract: Background Molecular tweezers (MTs) are broad-spectrum inhibitors of abnormal protein aggregation. A lead MT, called CLR01, has been demonstrated to inhibit the aggregation and toxicity of multiple amyloidogenic proteins in vitro and in vivo. Previously, we evaluated the effect of CLR01 in the 3 × Tg mouse model of Alzheimer’s disease, which overexpresses mutant human presenilin 1, amyloid β-protein precursor, and tau and found that subcutaneous administration of the compound for 1 month led to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 78 publications
0
12
0
Order By: Relevance
“…Tau seeds were prepared from PS19-mouse hippocampal extracts and added to biosensor cells for measurement of intracellular tau aggregation as described previously 19 . CLR16 was added 24 h after seeding.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tau seeds were prepared from PS19-mouse hippocampal extracts and added to biosensor cells for measurement of intracellular tau aggregation as described previously 19 . CLR16 was added 24 h after seeding.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, we also found that CLR01 inhibited dose-dependently the prion-like propagation of tau aggregates (tau seeding) in biosensor cells 17 . Moreover, the potential therapeutic effect of CLR01 has been demonstrated in multiple animal models of various proteinopathies including the triple-transgenic mouse model of Alzheimer’s disease (AD) 16 , a rat model of AD 18 , a mouse model of tauopathy 19 , zebrafish 12 , 20 and mouse 15 , 21 models of Parkinson’s disease (PD), a lamprey model of spinal cord injury 22 , and mouse models of transthyretin amyloidosis 14 , desmin-related cardiomyopathy 23 , amyotrophic lateral sclerosis 24 , multiple system atrophy 25 , and the lysosomal-storage disease Sanfilippo syndrome type A 26 .…”
Section: Introductionmentioning
confidence: 99%
“…During the analysis of tauopathy mouse brains 10 , we noticed rare exophers, similar to those described in c. elegans , which were attached to neuronal bodies via nanotubes (Fig. 1).…”
Section: Introductionmentioning
confidence: 52%
“…Thus, SU drugs may have potential In this study, P301S transgenic mice was used which is characterized by development of NFT and tau pathology from 3 months of age and previously showed evident pathology with various staining antibodies against tau protein on similar time plan of our study (Hollerhage et al 2014;Allen et al 2002). These mice demonstrated significant motor impairment, anxiety like behavior, reduced exploration when compared to WT (Watt et al 2020;Sun et al 2020;Di et al 2021;Zampar and Wirths 2021) and exhibit behavioral abnormalities that resemble deficits in human tauopathies (Takeuchi et al 2011).Based on previous studies with this experimental model of tauopathy, tau pathology starts by the third month of age, it then increases till reaching the highest level in 5-6 months, however, by that time animals are totally incapacitated so there is difficulty in behavioral tests assessment (Hollerhage et al 2014). Hence, experiment of the current study started on 3rd month of age and proceeded for 21 days, where we can find evident pathology when sacrificed yet preserving locomotion of the animals and decreasing mortalities.…”
Section: Discussionmentioning
confidence: 88%